Effect of Short Training on Vaginal Fluid Microscopy (Wet Mount) Learning. Issue 2 (April 2015) - Donders, Gilbert G.G.; Marconi, Camila; Bellen, Gert; Donders, Francesca; Michiels, Thirsa
<x xml:space="preserve">Abstract</x> Objective Is it feasible to learn the basics of wet mount microscopy of vaginal fluid in 10 hours? Materials and Methods This is a pilot project wherein 6 students with different grades of education were invited for being tested on their ability to read wet mount microscopic slides before and after 10 hours of hands-on training. Microscopy was performed according to a standard protocol (Femicare, Tienen, Belgium). Before and after training, all students had to evaluate a different set of 50 digital slides. Different diagnoses and microscopic patterns had to be scored. κ indices were calculated compared with the expert reading. Results All readers improved their mean scores significantly, especially for the most important types of altered flora (p < .0001). The mean increase in reading concordance (κ from 0.64 to 0.75) of 1 student with a solid previous experience with microscopy did not reach statistical significance, but the remaining 5 students all improved their scores from poor performance (all κ < 0.20) to moderate (κ = 0.53, n = 1) to good (κ > 0.61, n = 4) concordance. Reading quality improved and reached fair to good concordance on all microscopic items studied, except for the detection of parabasal cells and cytolytic flora. Conclusions Although further improvement is still possible, a short training course of 10 hours enables vast improvement on wet mount microscopy accuracy and results in fair to good concordance of the most important variables of the vaginal flora compared to a reference reader.